Academic Performance of Senior High School Students in Pre-Calculus - Padernal, Rogie E.; Diego, Crispina V. (Philippine Social Science Journal, 2020)
Knowledge in Pre-Calculus depends on students’ understanding of Algebra and Trigonometry. The result of the Program for International Students Assessment (PISA) in 2018 disclosed that the Philippines ranked the second-lowest in Mathematics assessment and indicated low performance in advanced subjects such as Calculus. Hence, the paper described the level of academic performance of senior high school students in a maritime school in Bacolod City during the school year 2019-2020. Likewise, it aimed to determine the relationship between the students’ demographics and the level of academic performance in Pre-Calculus. Furthermore, it is intended to test the correlation and predictive capability of the school of origin and entrance examination scores in the academic performance of students in Pre-Calculus.